Melatonin Plays a Critical Protective Role in Nicotine-Related Abdominal Aortic Aneurysm - Duan, Liren; Li, Shenli; Wang, Lei; Jing, Yuchen; Li, Guangxin; Sun, Yaodong; Sun, Weifeng; Li, Yalun; Zhao, Lin; Xin, Shijie (Frontiers in Physiology, 2020)
Aim: Smoking is a major risk factor for abdominal aortic aneurysm (AAA). Among the components of smoke, nicotine is known to exert pro-atherosclerotic, prothrombotic, and proangiogenic effects on vascular smooth muscle cells (VSMCs). The current study was designed to investigate the mechanisms through which nicotine induces vascular wall dysfunction and to examine whether melatonin protects against nicotine-related AAA. Methods: In this study, an enzyme-linked immunosorbent assay (ELISA) was used to measure melatonin and TNF-α levels, as well as total antioxidant status (TAS), in patients with AAA. We established a nicotine-related AAA model and explored the mechanisms underlying the therapeutic effects of melatonin. Tissue histopathology was used to assess vascular function, while western blotting (WB) and immunofluorescence staining were performed to detect protein expression. Results: We observed melatonin insufficiency in the serum from patients with AAA, particularly smokers. Moreover, melatonin level was positively correlated with antioxidant capacity. In the in vivo model, nicotine accelerated AAA expansion and destroyed vascular structure. Furthermore, OPN, LC3II, p62, matrix metalloproteinase-2 (MMP-2), matrix metalloproteinase-9 (MMP-9), NF-κB p65, TNF-α, phosphorylated AKT, and phosphorylated mTOR levels were increased, in vivo, following nicotine treatment, while SM22α and α-SMA levels were reduced. Additionally, melatonin attenuated the effects of nicotine on AAA and reversed changes in protein expression. Moreover, melatonin lost its protective effects following bafilomycin A1-mediated inhibition of autophagy. Conclusion: Based on our data, melatonin exerts a beneficial effect on rats with nicotine-related AAA by downregulating the AKT-mTOR signaling pathway, improving autophagy dysfunction, and restoring the VSMC phenotype.